Nocturnal enuresis among children in Morogoro region in Tanzania: A cross-sectional survey (Tanzania Medical Journal, 2020)
BackgroundEnuresis is common childhood disorders which affecting quality of life of children and causing significant psychosocial disturbances to children and their families. This condition has been widely reported globally with increasing data from sub-Saharan African region. In Tanzania there is no reports on its magnitude and therefore this study was carried out with the aim of determine the prevalence of this condition among children in Tanzania.MethodsThis was a community based cross-sectional study conducted among children aged between 5 and 14 years recruited from 12 streets in Morogoro Municipality in Tanzania. Standardized Swahili questionnaire was used to collect data including socio-demographic details of parents, children and presence of enuresis. Socio-demographic data included age of the child, sex, level of education of the parents, education of the child, presence of bed wetting, history of enuresis in the family.ResultsFive hundred and ten children were recruited into this study out of which 271 (53.1%) were females and mean age of study participants was 9±2.8 years. Enuresis was noted in 19% (97/510) of children, 68% (66/97) and 32% (31/97) had primary and secondary enuresis respectively. Significantly higher prevalence rates of enuresis were noted for children aged below 8 years 26.4% (43/162) and those with family history of enuresis 47% (18/38) with p values of 0.01 and < 0.001 respectively. Forty-one (42.3%) out of 97 respondents whose children had enuresis reported to have punished their children and only 21.4% (20/97) reported to have sought treatment for their children.ConclusionsEnuresis is common among children in Tanzania particularly those with positive family history. Punishment to children with enuresis was noted in this study and only one in five parents/guardians sought treatment for their affected children. Therefore, there is a need for initiatives for raising community awareness about enuresis in TanzaniaKey words: Enuresis in children, prevalence of enuresis in Tanzania, factors affecting enuresis in children.